EFFECT OF E-SERVICE QUALITY ON REPURCHASE INTENTIONS THROUGH CUSTOMER SATISFACTION ON SHOPEE CUSTOMERS IN MAKASSAR CITY - Damayanti, Irma; Kadir, Nuraeni; Toaha, Muhammad (Scientium Management Review, 2022)
This study aims to determine the effect of e-service quality on customer intentions to repurchase, through Shopee customer satisfaction in Makassar City. Quantitative methods are carried out to obtain research data, where later the data is primary data from distributing questionnaires to research objects. In the process, Shopee customers in Makassar City are used as the population in the study. The sample needed in the study was taken by purposive sampling technique with 385 sample respondents. Regression analysis using the PLS (Partial Least Square) method was used with the help of software in the form of SmartPLS3.0. The results showed that e-service quality can affect customer satisfaction, e-srvice quality affects repurchase intentions, customer satisfaction has a significant and positive effect on repurchase intentions and e-service quality has a significant and positive effect on repurchase intentions through satisfaction.